IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING WORD WALLS STRATEGY AND ALPHABOXES STRATEGY TO UNDERSTAND DESCRIPTIVE TEXT - Mansye Sekewael; Wanti Josinta Maria Leni (University of Kuningan, 2015)
The purpose of this research was to measure how far the Words Walls Strategy and Alphaboxes Strategy can improve students’ vocabulary mastery in understanding descriptive text. This was the kind of action research where the writer tried to collaborate his idea with the English teacher of the seventh grade of SMP Naskat Maria Mediatrix Ambon to gain the data of his research. the writer conducted his research at the first grade of SMP Naskat Maria Mediatrix in 2014/2015 Academic year. There are 22 students at that grade as the subjects of this research. In applying those strategies, There were two cycles: the first cycle consisted of six meetings where three meetings for use of Word Walls Strategy and Alphaboxes Strategy was sucessful in improving students’ vocabulary mastery in implementing Words Walls Strategy and another three meetings for the Alphaboxes strategy. For the second cycle, the writer used four meetings for applying both strategies. The writer used the students’ test result to measure the improvement of their vocabulary achievement. The writer found out that there were a significant differences scores after implementing both strategies. It proved that the students’ understanding of descriptive text well toward those strategies.Keywords: vocabulary mastery, word walls strategy, alphaboxes strategy, descriptive text .